Validation of a Simple 0 to 10 Numerical Score (IBD-10) of Patient-reported Inflammatory Bowel Disease Activity for Routine Clinical Use. Issue 8 (August 2016) - Subramanian, Sreedhar; Asher, Rebecca; Weston, William; Rimmer, Michael; McConville, Adam; Malin, Alex; Jackson, Richard; Collins, Paul; Probert, Chris; Dibb, Martyn; Rhodes, Jonathan M.
Abstract : Background: Various physician- and patient-reported instruments exist for quantification of disease activity in inflammatory bowel diseases (IBD) but none are widely used in routine clinical practice. A simple patient-reported outcome measure might help inform clinical decision making. We evaluated a patient-reported 0 to 10 score of IBD activity (IBD-10) by correlation with conventional multicomponent activity indices. Methods: A single-center prospective cross-sectional study was conducted in ambulant patients with IBD. Patients were asked to verbally rate the control of Crohn's disease (CD) or ulcerative colitis (UC) on a numerical scale from 0 to 10, with 10 indicating perfect control. Disease activity was assessed using Harvey–Bradshaw index for CD and simple clinical colitis activity index for UC. Results: A total of 405 patients were included, of whom 209 (52%) had CD and 196 (48%) had UC. The median age was 41 (interquartile range, 27–55) years. IBD-10 correlated well with Harvey–Bradshaw Index ( r s = −0.69, P < 0.001) and simple clinical colitis activity index ( r s = −0.79, P < 0.001). An IBD-10 score of ≥7 predicted remission (defined by Harvey–Bradshaw index/simple clinical colitis activity index) with 90% sensitivity (95% confidence interval [CI], 86–94) and 75% specificity (95% CI, 67–82). The discriminatory ability of IBD-10 for remission was better for UC (area under the receiver operating characteristic curve, 0.93; 95% CI, 0.89–0.97) than for CD (area under the receiver operating characteristic curve, 0.86; 95% CI, 0.81–0.91; P = 0.035). An IBD-10 score of <7 correlated with treatment escalation. Conclusions: The IBD-10 score correlates well with more complex clinical activity indices. Correlation was less strong for CD than for UC, possibly reflecting a weaker link in CD between stool frequency and the patient perspective of disease activity. The IBD-10 score could readily be used in routine clinical practice.